TNF-α signalling and inflammation: interactions between old acquaintances - Zelova, Hana; Hosek, Jan (Inflammation research, 2013)
Introduction Inflammation is a very important part of innate immunity and is regulated in many steps. One such regulating step is the cytokine network, where tumor necrosis factor α (TNF-α) plays one of the most important roles. Methods A PubMed and Web of Science databases search was performed for studies providing evidences on the role of TNF-α in inflammation, apoptosis, and cancer. Results and Conclusion This review concisely summarizes the role of this pro-inflammatory cytokine during inflammation. It is focused mainly on TNF-α intracellular signaling and its influence on the typical inflammatory features in the organism. Being one of the most important pro-inflammatory cytokines, TNF-α participates in vasodilatation and edema formation, and leukocyte adhesion to epithelium through expression of adhesion molecules; it regulates blood coagulation, contributes to oxidative stress in sites of inflammation, and indirectly induces fever. The connection between TNF-α and cancer is mentioned as well.